2020
DOI: 10.12688/aasopenres.13107.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of a mutation-specific genotyping method to assess for HIV-1 drug resistance in antiretroviral-naïve HIV-1 Subtype C-infected patients in Botswana

Abstract: Background: HIV-1 drug resistance poses a major threat to the success of antiretroviral therapy. The high costs of available HIV drug resistance assays prohibit their routine usage in resource-limited settings. Pan-degenerate amplification and adaptation (PANDAA), a focused genotyping approach based on quantitative PCR (qPCR), promises a fast and cost-effective way to detect HIV drug resistance mutations (HIVDRMs).  Given the high cost of current genotyping methods, we sought to use PANDAA for screening key HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Another interesting technology is the pan-degenerate amplification and adaptation (PANDAA) technology, which is based on quantitative PCR and uses extremely degenerate primers that target specific mutation sites and can cope with high HIV diversity next to the mutation site [ 53 ]. This technology has been tested in several settings [ 54 , 55 ] and shows high specificity and sensitivity. However, the need for a quantitative PCR instrument remains a challenge for POC applications.…”
Section: Technologies For Hiv Drug Resistance Testingmentioning
confidence: 99%
“…Another interesting technology is the pan-degenerate amplification and adaptation (PANDAA) technology, which is based on quantitative PCR and uses extremely degenerate primers that target specific mutation sites and can cope with high HIV diversity next to the mutation site [ 53 ]. This technology has been tested in several settings [ 54 , 55 ] and shows high specificity and sensitivity. However, the need for a quantitative PCR instrument remains a challenge for POC applications.…”
Section: Technologies For Hiv Drug Resistance Testingmentioning
confidence: 99%
“…In a traditional qPCR reaction, the binding of probes that are not in perfect complementation to the template are unstable and can produce false-negative results. In contrast, the PANDAA assay addresses high sequence variability through normalization of probe-binding regions, as seen in Figure 1 B. PANDAA primers have two main features: (1) a pan-degenerate region (PDR) containing degenerate bases to account for nucleotide variability and (2) an adaptor region (AR) that matches the probe-binding regions flanking the mutation of interest [ 24 ].…”
Section: Technologies Attempted For Hivdr Poctmentioning
confidence: 99%
“…The results demonstrated that PANDAA rendered excellent sensitivity (95~98%) and specificity (83~100%), although the readouts fluctuated among assays targeting different HIVDRMs. Maraupala et al conducted another study to test the diagnostic accuracy of PANDAA against Sanger in a cohort of patients from Botswana to use the assay as an alternative approach for rapid HIVDR test, and high concordance was observed between the data obtained from the two compared assays [ 24 ]. This positions PANDAA as a promising assay for HIVDR, although further refinement is required to meet the ASSURED criteria [ 7 ].…”
Section: Technologies Attempted For Hivdr Poctmentioning
confidence: 99%
“…Figshare: Use of a mutation-specific genotyping method to assess for HIV-1 drug resistance in antiretroviral-naïve HIV-1 Subtype C-infected patients in Botswana; https://doi.org/10.6084/m9.figshare.12644930 23 .…”
Section: Data Availabilitymentioning
confidence: 99%